Stubborn structures : reconceptualizing post-communist regimes - Magyar, Bálint, 1952- (Central European University Press, 2019)
The present volume represents a major step forward in the effort to understand post-communist politics in ways that escape the procrustean bed of theory oriented primarily to the democratization research agenda.